The Efficacy and Safety of Medical and Surgical Therapy in Patients With Primary Hyperparathyroidism: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials. (17th October 2022) - Ye, Zhikang; Silverberg, Shonni J.; Sreekanta, Ashwini; Tong, Kyle; Wang, Ying; Chang, Yaping; Zhang, Mengmeng; Guyatt, Gordon; Tangamornsuksun, Wimonchat; Zhang, Yi; Manja, Veena; Bakaa, Layla; et al.
ABSTRACT: Both medical and surgical therapy represent potential management options for patients with asymptomatic primary hyperparathyroidism (PHPT). Because uncertainty remains regarding both medical and surgical therapy, this systematic review addresses the efficacy and safety of medical therapy in asymptomatic patients or symptomatic patients who decline surgery and surgery in asymptomatic patients. We searched Medline, Embase, Cochrane Central Register of Controlled Trials, and PubMed from inception to December 2020, and included randomized controlled trials in patients with PHPT that compared nonsurgical management with medical therapy versus without medical therapy and surgery versus no surgery in patients with asymptomatic PHPT. For surgical complications we included observational studies. Paired reviewers addressed eligibility, assessed risk of bias, and abstracted data for patient‐important outcomes. We conducted random‐effects meta‐analyses to pool relative risks and mean differences with 95% confidence intervals and used Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) to assess quality of evidence for each outcome. For medical therapy, 11 trials reported in 12 publications including 438 patients proved eligible: three addressed alendronate, one denosumab, three cinacalcet, two vitamin D, and two estrogen therapy. Alendronate, denosumab, vitamin D, and estrogen therapy all increased bone density. Cinacalcet probably reduced serum calcium and parathyroid hormone (PTH) levels. Cinacalcet and vitamin D may have a small or no increase in overall adverse events. Very‐low‐quality evidence raised the possibility of an increase in serious adverse events with alendronate and denosumab. The trials also provided low‐quality evidence for increased bleeding and mastalgia with estrogen therapy. For surgery, six trials presented in 12 reports including 441 patients proved eligible. Surgery achieved biochemical cure in 96.1% (high quality). We found no convincing evidence supporting an impact of surgery on fracture, quality of life, occurrence of kidney stones, and renal function, but the evidence proved low or very low quality. Surgery was associated with an increase in bone mineral density. For patients with symptomatic and asymptomatic PHPT, who are not candidates for parathyroid surgery, cinacalcet probably reduced serum calcium and PTH levels; anti‐resorptives increased bone density. For patients with asymptomatic PHPT, surgery usually achieves biochemical cure. These results can help to inform patients and clinicians regarding use of medical therapy and surgery in PHPT. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).